A NEW HIGH-PERFORMANCE LIQUID CHROMATOGRAPHY METHOD FOR THE SEPARATION AND SIMULTANEOUS QUANTIFICATION OF EPTIFIBATIDE AND ITS IMPURITIES IN PHARMACEUTICAL INJECTION FORMULATION - GIRIJA, K. SRI; KASIMALA, BIKSHAL BABU; ANNA, VENKATESWARA RAO (International Journal of Applied Pharmaceutics, 2021)
Objective: The objective of the present study is to develop a stability-indicating reverse-phase high-performance liquid chromatography (RP-HPLC) method for qualitative and quantitative determination of Eptifibatide and its impurities in bulk and pharmaceutical dosage forms. Methods: The chromatographic separation was carried on Phenomenex Luna C18 column (250 mm×4.6 mm; 5µ id) as stationary phase, methanol and phosphate buffer at pH 6.4 in the ratio of 65:45 (v/v) as mobile phase at flow rate of 1.0 ml/min, Ultra Violet (UV) detection was carried at the wavelength of 236 nm and the analysis was completed with a run time of 15 min. Results: In the developed conditions, the retention time of Eptifibatide and its impurities 1 and 2 were found to be 3.35, 4.93 and 8.18 min, respectively. The method was validated for system suitability, range of analysis, precision, specificity, stability and robustness. Spiked recovery at 50%, 100% and 150% was carried for both standard and impurities and the acceptable % recovery of 98-102 was observed for Eptifibatide and both impurities studied and the % Relative standard deviation (RSD) in each spiked level was found to be less than 2. Stability tests were done through the exposure of the analyte solution to five different stress conditions i. e expose to 1N Hydrochloric acid (HCl), 1 N Sodium hydroxide (NaOH), 3% Hydrogen peroxide (H2O2), 80 °C temperature to UV radiation. In all the degradation conditions, standard drug Eptifibatide was detected along with both the impurities studied and the degradation products were successfully separated. In the formulation analysis, there is no other chromatographic detection of other impurities and formulation excipients. Conclusion: The developed method was found to be suitable for the quantification of Eptifibatide and can separate and analyse impurities 1 and 2.